Autonomy of Modern Russian Universities: Rectors' Attitude - D. A. Endovitskiy; Yu. A. Bubnov; K. M. Gaidar (Moscow Polytechnic University, 2020)
The problem of University autonomy goes back centuries. However, it has not lost its relevance today, and is far from final resolution. This problem has been solved in different ways in different historical periods and in different countries. There is no unambiguity in the approaches to its development even today. It is particularly significant for modern Russia, which is faced with the task of achieving the competitiveness of domestic higher education in the global educational space and ensuring its high-quality functioning, which would become a solid foundation for further progress and prosperity of the country. The authors highlight a new aspect in the study of this problem, namely, the perception of the state of autonomy of Russian universities by their rectors. At the same time, it is emphasized that the subjective and psychological aspect of the issue is no less important than the study of legal or economic aspects, since the opinion of rectors reflects the consolidated position of thousands of higher school employees whose social well-being is a significant factor in the effectiveness of universities. Based on the survey of rectors of regional universities, the article reveals some general trends and specific positions of those heads of higher education institutions that indicate a narrowing of University autonomy at the present time, and those who consider its current state to be satisfactory and stable.